(untitled) (Journal of the College of Basic Education, 2022)
The aim of the present study is to identify The Strategy R.E.A.C.T Efficiency for the Complex Thinking Skills in Math for intermediate second -Year students ,to achive this target I admit two zero theories. The experiment was applied to the study sample in the students of the second grade n the Al farazadq secondary school for boys belonging to the General Directorate for the education of the second Rusafa in Baghdad, (31) students to represent the control group, (38) students were selected to represent the experimental group, The Complex Thinking Skills test was prepared from (35) paragraphs, The test consists of (24) objective paragraphs of the type (multiple choice) and (11) paragraphs, Its Validity had been ensure by the Statistical Analysis. The results had been shown the success of the experimental group who studied according The Stratigic R.E.A.C.T upon the control group for the test of the Complex Thinking Skills with these results, many recommendtons and Conclusions had been achived